Catalytic Etherification of Glycerol to Diglycerol Over Heterogeneous Calcium-Based Mixed-Oxide Catalyst: Reusability and Stability - Gholami, Z. (Taylor and Francis Ltd., 2015)
The activities of different heterogeneous alkaline-earth metal oxide catalysts and mixed-metal oxide catalysts were investigated. Glycerol etherification was carried out at 250Â°C in a three-necked glass reactor vessel at atmospheric pressure. In a typical experiment, 50Â g of anhydrous glycerol was loaded into the reactor. Then, 2Â wt. of catalyst was added to the reactor. The reactor was then heated to the appropriate reaction temperature in nitrogen atmosphere under continuous stirring. The heterogeneous CaO catalyst showed the highest catalytic conversion (72) compared with other alkaline-earth metal oxides, with a diglycerol yield of 19. The highest glycerol conversion of 96 and diglycerol yield of 52 were observed for the mixed-metal oxide catalyst (Ca1.6Al0.4La0.6O3). Reusability and stability of this catalyst were tested. The ICP-AES analysis was performed to confirm the leaching of the metal species in the liquid phase of the reaction mixture. Â© 2015, Copyright Â© Taylor & Francis Group, LLC.